STIMULASI PERTUMBUHAN Lactobacillus casei subsp. rhamnosus PADA MEDIA YANG DISUPLEMENTASI TEPUNG REBUNG BAMBU TABAH (Gigantochloa nigrociliata Buse-Kurz) - Ary Subakti, Ketut Agus; Semadi Antara, Nyoman; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 1 (2016): Maret)
Shoots of tabah bamboo (Gigantochloa nigrociliata Buse-Kurz) are known containing dietary fiber and oligosaccharides as a prebiotic potential. The components contained in the bamboo shoots are expected to enhance the growth of the microflora of the digestive tract including lactic acid bacteria (LAB). This study was conducted to determine the ability of the bamboo shoot flour as a substrate to stimulate the growth of Lactobacillus casei subsp. rhamnosus. In vitro experiment was conducted in the laboratory by treatment of fermentation time. The media used was Tr-YP media, which was yeast-peptone media added by 2 g bamboo shoots powder per 100 ml. Fermentation was carried out at 37°C with a fermentation time of 0 hours to 24 hours. The results showed that during the fermentation the growth of Lactobacillus casei subsp. rhamnosus were stimulated by the media that supplemented by bamboo shoot powder. The growth of the bacteria were followed by the decrease in pH. Total Lactobacillus casei subsp. rhamnosus after 12 hours fermentation was 5,5x10 8 CFU/ml and the pH was 5,13. [Keywords]: Gigantochloa nigrociliata, Lactobacillus casei subsp. rhamnosus, flour bamboo shoots
Keywords: 87,